Stigma, depression, quality of life, and the need for psychosocial support among people with tuberculosis in Indonesia: A multi-site cross-sectional study. - Ahmad Fuady; Bustanul Arifin; Ferdiana Yunita; Saidah Rauf; Agus Fitriangga; Agus Sugiharto; Finny Fitry Yani; Helmi Suryani Nasution; I Wayan Gede Artawan Eka Putra; Muchtaruddin Mansyur; Tom Wingfield (PLOS Global Public Health)
Stigma towards people with tuberculosis (TB-Stigma) is associated with other psychosocial consequences of TB including mental illness and reduced quality of life (QoL). We evaluated TB-Stigma, depression, QoL, and the need for psychosocial support among adults with TB in Indonesia, a high TB burden country. In this primary health facility-based survey in seven provinces of Indonesia, from February to November 2022, we interviewed adults receiving (a) intensive phase treatment for drug-susceptible (DS) TB at public facilities, (b) treatment at private facilities, (c) those lost to follow up (LTFU) to treatment, and (d) those receiving TB retreatment. We used our previously validated Indonesian TB-Stigma Scale, Patient Health Questionnaire-9, and EQ-5D-5L to measure TB-Stigma, depression, and QoL. Additional questions assessed what psychosocial support was received or needed by participants. We recruited and interviewed 612 people, of whom 60.6% (96%CI 59.6-64.5%) experienced moderate TB-Stigma. The average TB-Stigma scores were 19.0 (SD 6.9; min-max 0-50; Form A-Patient Perspective) and 23.4 (SD 8.4, min-max 0-50; Form B-Community Perspective). The scores were higher among people receiving treatment at private facilities (adjusted B [aB] 2.48; 0.94-4.03), those LTFU (aB 2.86; 0.85-4.87), males (aB 1.73; 0.59-2.87), those losing or changing job due to TB (aB 2.09; 0.31-3.88) and those living in a rural area (aB 1.41; 0.19-2.63). Depression was identified in 41.5% (95% CI 37.7-45.3%) of participants. Experiencing TB-Stigma was associated with moderately severe to severe depression (adjusted odds ratio [aOR] 1.23; 1.15-1.32) and both stigma and depression were associated with lower QoL (aB -0.013; [-0.016]-[-0.010]). Informational (20.8%), emotional (25.9%) and instrumental (10.6%) support received from peers or peer-groups was limited, and unmet need for such support was high. There is a sizeable and intersecting burden of TB-Stigma and depression among adults with TB in Indonesia, which is associated with lower QoL. Participants reported a substantial unmet need for psychosocial support including peer-led mutual support groups. A community-based peer-led psychosocial support intervention is critical to defray the psychosocial impact of TB in Indonesia.